The Effect of Halal Labelization, Price, and Promotions on The Purchase Decision of Samyang Noodles in Greater Jakarta - Kaban, Reny Fitriana (Journal of Islamic Economics and Social Science (JIESS), 2022)
This study uses independent variables, namely halal labeling, price, and promotion to determine and analyze the effect of these three variables on consumer purchasing decisions for Samyang noodles in JABODETABEK. This study uses quantitative methods and data processing methods using multiple linear regression analysis. The source of the population taken by the researchers came from Samyang noodle consumers who had bought and eaten food products from the Samyang Food company in Indonesia. For the number of samples in this study using as many as 100 respondents from Samyang noodle consumers in JABODETABEK. The data collection instrument studied was obtained by distributing questionnaires. To determine the magnitude of the influence of the variables in this study, the analytical technique used is multiple linear analysis. SPSS (Statistical Package for Social Sciences) software version 20 was the tool used to process this research. The results of the tests carried out show that the variables of halal labeling, price, and promotion have a positive and significant effect partially and simultaneously on purchasing decisions for Samyang noodles in JABODETABEK.